2017
DOI: 10.1007/s00431-017-2867-2
|View full text |Cite
|
Sign up to set email alerts
|

Conservative treatment in uncomplicated acute appendicitis: reassessment of practice safety

Abstract: When applying rigorous criteria for children with uncomplicated appendicitis, a high success rate can be achieved with conservative treatment. Those who fail conservative treatment have a benign medical course without serious complications. Intraluminal fluid may increase risk for conservative treatment failure. What is Known: • Conservative treatment in uncomplicated acute appendicitis is a reasonable alternative to appendectomy. What is New: • Using rigorous criteria for conservative treatment in uncomplicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 22 publications
2
22
0
1
Order By: Relevance
“…We hope to be able to add more information on ultrasound findings, for instance appendiceal intraluminal fluid in ultrasound examinations as this feature was considered important for differentiating between AUA and ACA. 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hope to be able to add more information on ultrasound findings, for instance appendiceal intraluminal fluid in ultrasound examinations as this feature was considered important for differentiating between AUA and ACA. 15…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] However, recent and upcoming paediatric studies have confirmed or the aim to support that nonoperative management with antibiotics is a feasible and safe option for patients with acute uncomplicated phlegmonous appendicitis while appendicectomy remains the appropriate treatment for acute complicated appendicitis defined by gangrene or perforation. [10][11][12][13][14][15] Of note, conservative treatment leads to symptom relief just after one day and thus is not inferior to appendicectomy concerning this matter. 16 Therefore, the use of ultrasound for the pre-operative differentiation between gangrenous/perforated appendicitis and uncomplicated appendicitis is important, especially in regard of defining treatment groups.…”
Section: Introductionmentioning
confidence: 99%
“…Appendicolith is a known risk-factor for non-operative treatment of appendicitis [ 20 , 36 , 37 ], and its surgical treatment is recommended [ 38 ]. Before conducting this study, the authors did not expect that appendicolith was also a risk-factor in surgical treatment of appendicitis; therefore, they did not manage patients with appendicolith specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Non-operative method seems to be effective in management of acute uncomplicated appendicitis. [3][4][5][6][7] Accurate selection of patients whose appendix inflammation could be controlled by the use of antibiotics may improve the success rate of nonsurgical treatment.…”
Section: Introductionmentioning
confidence: 99%